Increased inosine levels in drug‐free individuals with at‐risk mental state: A serum metabolomics study. Issue 3 (28th March 2021) - Uekusa, Shusuke; Onozato, Mayu; Umino, Maho; Sakamoto, Tatsuya; Ichiba, Hideaki; Tsujino, Naohisa; Funatogawa, Tomoyuki; Tagata, Hiromi; Nemoto, Takahiro; Mizuno, Masafumi; Fukushima, Takeshi
Abstract: Aim: At‐risk mental state (ARMS) has been recently attracting attention with respect to the improvement of the management and outcome of psychiatric diseases, such as schizophrenia. Since only a few studies have reported on biological alterations in ARMS, serum metabolomics was carried out in ARMS subjects and healthy controls using liquid chromatography with high‐resolution mass spectrometry. Methods: Serum samples were collected from ARMS subjects ( n  = 24; male: 12; female 12) and age‐ and sex‐matched healthy controls ( n  = 23 male: 11, female: 12). After serum pre‐treatment, liquid chromatography with high‐resolution mass spectrometry was performed. Multivariate analyses, such as orthogonal partial least‐squares discriminant and volcano plot analyses, were performed. Results: Serum inosine, lactate, taurine, 2, 3‐dihydroxypropanoate and glutamate levels differed between the two groups. A significant increase in inosine levels was detected in the positive‐ and negative‐ion modes; however, significant differences were not observed in the levels of other purine‐related metabolites (hypoxanthine, xanthine and urate) between the two groups. Conclusion: Increased inosine levels may serve as biological markers for ARMS, in addition to alterations in the levels of lactate and certain amino acids.